Comparing the efficacy of different methods in assessing cervical stromal invasion in endometrial carcinoma: a retrospective study of 2,020 patients - Yang, Ying; Ye, Zhijun; Zhao, Yifei; Li, Zhengyu (Frontiers in Oncology, 2025)
PurposeThis study aimed to assess the preoperative diagnostic efficacy of magnetic resonance imaging (MRI), computed tomography (CT), and endometrial biopsy for cervical stromal invasion (CSI) in endometrial carcinoma (EC) and to discuss the influencing factors of CSI.Material and methodsA total of 2,020 patients with EC were retrospectively analyzed in a tertiary hospital. Basic patient information, clinical pathology, and laboratory indicators were collected and analyzed. Using the postoperative pathological diagnosis as the gold standard, the diagnostic efficacies of different preoperative methods were analyzed. Additionally, influencing factors of CSI were examined by univariate and multivariate analyses.ResultsThe sensitivity (Sens.), specificity (Spec.), accuracy (Acc.), diagnostic odds ratio (DOR), Youden’s index, and Kappa value of the MRI vs. CT groups were 49.50% vs. 56.74%, 92.24% vs. 79.09%, 87.70% vs. 76.15%, 11.60 vs. 4.93, 0.42 vs. 0.36, and 0.392 vs. 0.256 (p < 0.001), respectively. The Sens., Spec., Acc., DOR, Youden’s index, and Kappa value of the endometrial biopsy group were 41.74%, 93.25%, 87.08%, 9.97, 0.35, and 0.363 (p < 0.001), respectively. CSI was associated with cancer antigen 125, myometrial invasion, adnexal invasion, parametrial invasion, lymph node metastasis, and progesterone receptor.ConclusionsMRI is relatively superior in assessing CSI, although diagnostic authenticity and consistency were unsatisfactory. Combining MRI and biopsy could improve diagnostic sensitivity, aiding in clinical decision making and prognostic prediction. Comprehensive consideration of high-risk factors for the occurrence of CSI may aid the diagnosis. Preoperative diagnostic methods of CSI in EC still need to be explored further to improve efficiency.